2015
DOI: 10.5194/angeo-33-547-2015
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of long-distance propagation of gravity waves under CAWSES India Phase II Programme

Abstract: Abstract. Coordinated measurements of airglow features from the mesosphere-lower thermosphere (MLT) region were performed at Allahabad (25.5 • N, 81.9 • E) and Gadanki (13.5 • N, 79.2 • E), India to study the propagation of gravity waves in 13-27 • N latitude range during the period June 2009 to May 2010 under CAWSES (Climate And Weather of Sun Earth System) India Phase II Programme. At Allahabad, imaging observations of OH broadband emissions and OI 557.7 nm emission were made using an all-sky imager, while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Examples are atomic oxygen density (Lednyts'kyy et al, 2014;Russell et al, 2005), vertical transport (Broadfoot and Gardner, 2001;Hays et al, 2003), mesospheric temperatures (Innis et al, 2001;Scheer and Reisin, 2007;Holmen et al, 2014;Parihar et al, 2017, and references cited therein), mesospheric winds (Lloyd et al, 1990), density and pressure (Takahashi et al, 2004), thermospheric temperatures and wind velocities (Cocks, 1983;Vila et al, 1998;Ford et al, 2006Ford et al, , 2008Nakamura et al, 2017), F region peak electron density and its height (Sahai et al, 1981;Makela et al, 2001), F region zonal drifts (Yao and Makela, 2007), etc. Often the derived parameters are then utilized to understand the behaviour of the emitting region, mainly its chemistry, dynamics and electrodynamics (Semenov, 1988;Fagundes et al, 2001;Makela et al, 2001Makela et al, , 2004Shiokawa et al, 2003;Scheer and Reisin, 2007;Ford et al, 2008;López-González et al, 2009;Parihar et al, 2013;Holmen et al, 2014). Other ground-based techniques include lidars and radars; however, airglow experiments remain a favourite due to their wellestablished simplicity, cost-effectiveness and capability for continuous operation on a longer timescale (Ford et al, 2008;Espy et al, 2011;Holmen et al, 2014;Scheer and Reisin, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Examples are atomic oxygen density (Lednyts'kyy et al, 2014;Russell et al, 2005), vertical transport (Broadfoot and Gardner, 2001;Hays et al, 2003), mesospheric temperatures (Innis et al, 2001;Scheer and Reisin, 2007;Holmen et al, 2014;Parihar et al, 2017, and references cited therein), mesospheric winds (Lloyd et al, 1990), density and pressure (Takahashi et al, 2004), thermospheric temperatures and wind velocities (Cocks, 1983;Vila et al, 1998;Ford et al, 2006Ford et al, , 2008Nakamura et al, 2017), F region peak electron density and its height (Sahai et al, 1981;Makela et al, 2001), F region zonal drifts (Yao and Makela, 2007), etc. Often the derived parameters are then utilized to understand the behaviour of the emitting region, mainly its chemistry, dynamics and electrodynamics (Semenov, 1988;Fagundes et al, 2001;Makela et al, 2001Makela et al, , 2004Shiokawa et al, 2003;Scheer and Reisin, 2007;Ford et al, 2008;López-González et al, 2009;Parihar et al, 2013;Holmen et al, 2014). Other ground-based techniques include lidars and radars; however, airglow experiments remain a favourite due to their wellestablished simplicity, cost-effectiveness and capability for continuous operation on a longer timescale (Ford et al, 2008;Espy et al, 2011;Holmen et al, 2014;Scheer and Reisin, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Around 825 nm, the quantum efficiency of the CCD detector is 70-80 % and the dark current is less than 0.001 e − pixel −1 s −1 . Parihar and Taori (2015) described this imaging system in detail. Optical filters for monitoring P 1 (2) line and P 1 (4) line had a bandwidth of ∼ 1.1 nm, while that of the 857.0 nm filter was ∼ 2.0 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique, the time series of the intensity of P 1 (2) line, P 1 (4) line and background emissions for five locations were recorded for further analysis. This process was described in detail in Parihar and Taori (2015). A typical example of such a generated intensity series of P 1 (2) Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…From the Indian sector, there are also several reports (e.g., Mukherjee 2003Pragati et al, 2010;Lakshmi Narayanan and Gurubaran, 2013;Parihar and Taori, 2015) which document the small-scale gravity wave characteristics. For example, using 5 months of OH airglow imager data from January to May 2008 at Allahabad (25.45 • N, 81.85 • E), Pragati et al (2010) reported that most of the small-scale gravity waves propagate to the north and northeast in March and May.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, during 2007 Lakshmi Narayanan and Gurubaran (2013) reported the seasonal variation of the gravity wave characteristics over Tirunelveli (8.71 • N, 77.81 • E). Recently, Parihar and Taori (2015) investigated the longdistance propagating gravity waves using the coordinated bi-station airglow data (Airglow photometer over Gadanki (13.5 • N, 79.2 • E) and all-sky airglow imager over Allahabad (25.5 • N, 81.9 • E)). They concluded that convection might be a source of the noted long-distance gravity wave events.…”
Section: Introductionmentioning
confidence: 99%